Proceedings of the 9th Annual Conference on Genetic and Evolutionary Computation 2007
DOI: 10.1145/1276958.1277377
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two models to generate hyper-heuristics for the 2d-regular bin-packing problem

Abstract: The idea behind hyper-heuristics is to discover some combination of straightforward heuristics to solve a wide range of problems. To be worthwhile, such combination should outperform the single heuristics. This paper presents two Evolutionary-Computation-based Models to produce hyperheuristics that solve two-dimensional bin-packing problems. The first model uses an XCS-type Learning Classifier System which learns a solution procedure when solving individual problems. The second model is based on a GA that uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…We use the Alea parallel and distributed job scheduling simulator built on top of the GridSim simulator [19,20]. The Alea simulator is an event-based modular simulator, composed of independent entities like a centralized scheduler, job generator, job submission system, and the resources.…”
Section: Methodsmentioning
confidence: 99%
“…We use the Alea parallel and distributed job scheduling simulator built on top of the GridSim simulator [19,20]. The Alea simulator is an event-based modular simulator, composed of independent entities like a centralized scheduler, job generator, job submission system, and the resources.…”
Section: Methodsmentioning
confidence: 99%
“…5.1). Unlike most of the evolutionary-based hyper-heuristic approaches proposed in the literature (Han and Kendall 2003;Ross et al 2004;Marín-Blázquez and Schulenburg 2006;Ersoy et al 2007;Burke et al 2007;Terashima-Marin et al 2007;Bader-El-Den and Poli 2008;Kumar et al 2008;Pillay 2008;Terashima-Marín et al 2008;Tay and Ho 2008), and in accordance with the new and unified classification of hyper-heuristics described in Burke et al (2010), we have proposed a hybrid heuristic selection approach whose general representation corresponds to a sophisticated, yet easy to understand, sequence of constructiveperturbative pairs of low-level heuristics which gradually construct and improve partial solutions.…”
Section: The Hyper-heuristic Frameworkmentioning
confidence: 99%
“…In the above categories, several evolutionary approaches have successfully been applied to a great amount of NP-hard problems (Han and Kendall 2003;Krasnogor and Gustafson 2004;Ross et al 2004;Özcan 2006;Bader-El-Den and Poli 2008;Ersoy et al 2007;Garrido and Riff 2007;Burke et al 2007;Poli et al 2007;Terashima-Marin et al 2007;Kumar et al 2008;Pillay 2008;Tay and Ho 2008). Considering the nature of the heuristic search space, the major contributions in heuristic selection methodologies are genetic/memetic algorithms and evolutionary classifier systems.…”
Section: Evolutionary Hyper-heuristic: Eh-dvrpmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has also shown that human competitive heuristics can be evolved for two dimensional strip packing problems [19], and heuristics designed by evolution for the three dimensional packing problem are compared to a human designed heuristic in [20]. A genetic algorithm is used to evolve hyper-heuristics for the two dimensional packing problem in [21], [22], [23], [24]. The evolved individual contains criteria to decide which packing heuristic to apply next, based on the properties of the pieces left to pack.…”
Section: Hyper-heuristicsmentioning
confidence: 99%